2021
DOI: 10.3389/fped.2020.613766
|View full text |Cite|
|
Sign up to set email alerts
|

Platelet Counts and Patent Ductus Arteriosus in Preterm Infants: An Updated Systematic Review and Meta-Analysis

Abstract: Background: A meta-analysis published in 2015 showed a significant association between low platelet counts in the first day(s) of life and risk of patent ductus arteriosus (PDA). The meta-analysis pooled data from 11 studies cohorts (3,479 preterm infants).Objective: To update the meta-analysis by adding new studies on the topic and including other platelet parameters different from platelet counts.Methods: PubMed/Medline and Embase databases were searched. Random-effects risk ratios (RR) and differences in me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…Furthermore, a higher platelet count (≥181 × 10 9 /L) before ibuprofen treatment was found to be independently associated with the closure of hsPDA in VLBW infants without concurrent infection. Since Echtler et al (16) first reported that platelets are crucial for ductus arteriosus closure in mice and premature infants, several studies also analyzed the association between low platelet and the patency of ductus arteriosus in preterm infants, yielding conflicting findings (8,(17)(18)(19)(20). Building up the complexity studies investigating whether platelet level affects the closure of PDA after pharmacotherapeutic agents also reported conflicting findings.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a higher platelet count (≥181 × 10 9 /L) before ibuprofen treatment was found to be independently associated with the closure of hsPDA in VLBW infants without concurrent infection. Since Echtler et al (16) first reported that platelets are crucial for ductus arteriosus closure in mice and premature infants, several studies also analyzed the association between low platelet and the patency of ductus arteriosus in preterm infants, yielding conflicting findings (8,(17)(18)(19)(20). Building up the complexity studies investigating whether platelet level affects the closure of PDA after pharmacotherapeutic agents also reported conflicting findings.…”
Section: Discussionmentioning
confidence: 99%
“…The methodology of this study is based on that of earlier studies of our group on risk factors for PDA [ 27 , 28 , 29 , 30 ]. The study was performed and reported according to the preferred reporting items for systematic reviews and meta-analyses (PRISMA) and meta-analysis of observational studies in epidemiology (MOOSE) guidelines [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…As in our previous meta-analyses [ 27 , 28 , 29 , 30 ], the studies were divided according to the way they considered small ductal shunts [ 27 , 28 , 29 , 30 ]. Studies comparing small + large PDA vs. closed DA were classified as reporting on “any PDA.” Studies comparing large PDA vs. small PDA + closed DA were classified as reporting on “hemodynamically significant PDA” (hsPDA).…”
Section: Methodsmentioning
confidence: 99%
“…In summary, the aforementioned studies (and recent metaanalyses) on platelet indices and PDA have revealed inconsistent or even conflicting results, which were probably, at least in part, due to differences in study designs, treatment protocols, and the definition of hsPDA (28,34). Furthermore, hematologic indices might be affected by several conditions, such as inflammation, hypoxia and/or volume status, and thus likely represent surrogate markers of neonatal well-being rather than being specific indicators of PDA/hsPDA, e.g., higher PDW values are thought to reflect altered platelet function/activation (35).…”
Section: Platelet Indices and Pdamentioning
confidence: 99%
“…However, it should be noted, that most studies were retrospective in nature, and thus, even the positive studies cannot conclude on any causality as relevant confounding factors might have been missed by the analyses. In addition, the remarkable heterogeneity in study design (selection criteria, genetic background, and timing of platelet counts), diagnostic protocols (timing of echocardiography and criteria used to define hemodynamic significance), and differences in treatment approaches (timing, dosage, and application route) may have influenced the comparability of the available studies (18,26,28).…”
Section: The Effects Of Thrombocytopenia and Platelet Transfusions Onmentioning
confidence: 99%